EXPLORING THE ANTECEDENTS OF UNIVERSITY STUDENTS’ ENTREPRENEURIAL INTENTION IN AN EMERGING COUNTRY - Poanto, Elysia; Sembel, Jacquelinda Sandra (Proceedings of the International Conference on Entrepreneurship (IConEnt), 2022)
An emerging country like, Indonesia requires the young generation to be educated in order to help the nation to recover stronger from the devastating impact of COVID 19 Pandemic. The country requires a lot of business and entrepreneurial activities to transform it into a country with a stronger and more resilient economy. The purpose of this research is to analyze the factors influencing the entrepreneurial intention of university students in Indonesia. The data was gathered through the use of a survey approach and the distribution of questionnaires. University students (New university entrants, bachelor's degrees, masters’ degrees, and doctorate degrees) studying in Indonesia are the target population for this study. Validity and reliability tests were performed in this study, and a pre-test with 32 respondents was conducted before the actual data collection. Furthermore, a total of 270 individuals were chosen as the sample size. Quantitative research was used, with judgmental sampling as the design sampling method. Moreover, the Partial Least Square Structural Equation Modeling with SmartPLS was used to scrutinize the data in this study (v. 3.3.7). The data show that all of the variables examined have a positive effect on entrepreneurial intention. However, having three supported hypotheses; Entrepreneurial Mindset, Entrepreneurial Education, Perceived Behavioral Control, and two unsupported hypotheses; Self-Competence and Subjective Norms.